Total Cerebral Small Vessel Disease Burden on MRI Correlates With Medial Temporal Lobe Atrophy and Cognitive Performance in Patients of a Memory Clinic - Fan, Yangyi; Shen, Ming; Huo, Yang; Gao, Xuguang; Li, Chun; Zheng, Ruimao; Zhang, Jun (Frontiers in Aging Neuroscience, 2021)
Abstract: Background: Cerebral small vessel disease (cSVD) and neurodegeneration are two main causes of dementia and are considered as distinct pathological processes. While evidence has shown overlaps and interactions between the two pathological pathways. Medial temporal atrophy (MTA) is considered a classic marker of neurodegeneration. We aim to investigate the relation of total cSVD burden and MTA on MRI using a total cSVD score, moreover to explore the impact of the two MRI features on cognition. Methods: Patients in a memory clinic were enrolled, who underwent brain MRI scan and cognitive evaluation within 7 days after the first visiting. MTA and total cSVD score were rated using validated visual scales. Cognitive function was assessed by MMSE and MoCA scale. Spearman correlation and regression models were used to test (i) the association between MTA and total cSVD score as well as each cSVD marker, and (ii)the correlation of the MRI features and cognitive status. Results: A total of 312 patients were finally enrolled, with a median age of 75.0 (66.0-80.0) years and 40.7% (127/312) male. All of them finished MRI and MMSE, 293 subjects finished MoCA. 71.8% (224/312) of the patients had at least one of the cSVD markers and 48.7% (152/312) of them had moderate-severe MTA. Total cSVD score was independently associated with MTA levels, after adjusting for age, gender, years of education and other vascular risk factors (OR 1.191, 95% CI 1.071-1.324, P=0.001). In regard to individual markers, significant association only existed between WMH and MTA after adjusting for factors above (OR 1.338, 95% CI 1.050-1.704, P=0.018). Both MTA and total cSVD score were independent risk factors for MMSE≤26 (MTA: OR 1.877, 95% CI 1.407-2.503, P＜0.001; total cSVD score: OR 1.474, 95% CI 1.132-1.921, P=0.004) and MoCA＜26 (MTA: OR 1.629, 95% CI 1.112-2.388, P=0.012; total cSVD score: OR 1.520, 95% CI 1.068-2.162, P=0.020). Among all the cSVD markers, microbleed was found significantly associated with MMSE≤26 while no marker was demonstrated a relation with MoCA＜26. Conclusions: cSVD was related to MTA in patients of memory clinic and both mentioned two MRI features had significant association with cognitive impairment.